Valores normativos de capacidades físicas para idosas residentes em Cuiabá-MT - Martins, Neusa Maria Carraro (2013)
Introduction: The paucity of literature on cutoffs for a portion of the physical tests applied to elderly undertakes understanding how these subjects are faced with a certain level of fitness. In this sense the proposition cutoffs, which qualitatively and quantitatively classify the physical capacities may provide grants to improve interventions. Objective: Considering this gap this research, had the objective of develop normative values of physical abilities for five-year periods for elderly residents in the city of Cuiabá-MT. Methods: The sample consisted of 461 women aged over 65 years. Physical tests were: agility (take and dress the shirt), flexibility (sit and reach), balance (one-leg right and left), muscular endurance (sit and stand) and isometric strength (legs and lower back, and scapular handgrip). The determination of values for the cutoffs for each test was performed by calculating the percentile ranking on very weak, weak, fair, good and very good. Subsequently we analyzed the variances between each performance through the test one way ANOVA with Tukey post hoc when appropriate. The level of significance was pre-set at 5%. Results: There was a statistically significant difference for all cutoffs in each physical test in five-year periods 65-69, 70-74, 75-79 and above 80 years, except for the very good performance in the tests and dynamometer scapular and take the dress shirt (p> 0.05). Conclusion: There are differences between the five-year periods for all physical tests, and thus, the qualitative cutoff values proposed here qualitative contribute to the classification of physical performance and, this way, contributes to the better targeting of proposals for intervention with this population.